Evaluation of proverb translation in Nahj al-Balagheh based on the theory of Peter Newmark (Dashti, Shahidi and Foladvand): ارزیابی ترجمه ضرب‌المثل‌ در نهج البلاغه بر اساس نظریه پیتر نیومارک. مطالعۀ موردی: (دشتی، شهیدی و فولادوند) (Journal of the College of Languages (JCL), 2023)
In addition to being a religious book with high human and moral themes, Nahj al-Balagha is considered a mirror of Arab culture and a literary masterpiece at the height of eloquence and eloquence, and because proverbs in the form of short, concrete and understandable phrases for everyone, experiences, thoughts and convey ideas, Imam Ali (AS) used it to facilitate the understanding of various political, social and moral concepts. In this article, we intend to criticize the way Dashti, Shahidi and Foladvand translated it by using Newmark's model due to the importance and cultural reflections of proverbs in understanding the cultural atmosphere governing Nahj al-Balagheh. In his evaluation model, Newmark divides cultural categories into five categories. While focusing on the fourth category, i.e. concepts, the current research has investigated the way of translating proverbs and comparing it with the methods provided by Newmark for the translation of cultural elements.چکیدهنهج‌البلاغه علاوه بر اینکه کتابی دینی با مضامین والای انسانی و اخلاقی است، آیینه فرهنگ عرب و شاهکاری ادبی در اوج فصاحت و بلاغت به شمار می‌رود و از آن روی که ضرب‌المثل‌ها در قالب عبارتی کوتاه، ملموس و قابل فهم برای همگان، تجربیات، افکار و اندیشه‌ها را انتقال می‌دهند، امام علی (ع) از آن برای تسهیل درک مفاهیم مختلف سیاسی، اجتماعی و اخلاقی بهره بُرده است. در این نوشتار ما برآنیم تا به دلیل اهمیت و بازتاب‌های فرهنگی بسزای ضرب‌المثل‌ها در فهم هر چه بهتر فضای فرهنگی حاکم بر نهج البلاغه، نحوه ترجمه آن توسط دشتی، شهیدی و فولادوند را با بکارگیری الگوی نیومارک به بوته نقد بنشانیم. نیومارک در الگوی ارزیابی خود، مقولات فرهنگی را به پنج دسته‌بندی می‌کند. پژوهش کنونی ضمن تمرکز بر دسته چهارم یعنی مفاهیم به بررسی نحوه ترجمه ضرب‌المثل و تطبیق آن با روش‌های ارائه شده توسط نیومارک برای ترجمه عناصر فرهنگی پرداخته است.